Leaving the ship but staying on board: a multiple case study of the voluntary shift from leader to teacher within the same educational institution - McLeod, Ian Alexander (Auckland University of Technology, 2009)
The New Zealand education system has undergone some two decades of substantial reform. There can be little doubt that this has brought significant change to the nature of what is expected of people occupying positions of leadership in schools and educational institutions (Ball, 2007; Bottery, 2004; Codd, 2005). Against this contextual backdrop, and in the researcher’s experience as a teacher and former holder of a position of leadership, there is an observable phenomenon of educational leaders stepping aside from position and yet continuing to work as teachers within the same workplace. Despite claims of a leadership ‘crisis’, and international acknowledgement of concern over the retention of educational leaders (Brooking, 2007; Brundrett & Rhodes, 2006; Fullan, 2005), the human experience of this phenomenon appears unrepresented in current research literature. The present study has sought to capture this experience through addressing the central research question “What is the lived experience of the voluntary relinquishing of the position of leader, yet choosing to remain within the same educational workplace?” In order to gather rich qualitative data, a descriptive multiple case study design was employed. In-depth unstructured interviews were carried out with eight educational leaders who had relinquished position within the contexts of New Zealand State Secondary Schools and Private Training Establishments, and chosen to continue working in these same contexts. The subsequent analysis drew on the tradition of hermeneutic interpretation (van Manen, 1990) to arrive at interpretations of the uniqueness of individual experiences, and offer understandings of the shared meanings of the experience in the form of essential themes. The key findings which emerged in this study were those of a sense of the ‘a-lone-ness’ of leadership, the ‘ready-suddenness’ of the decision to step aside, a seeking of ‘balance’ in the relinquishing of position, a powerful sense of ‘re-turning’ to the call of teaching, and varying degrees of ‘ease’ and ‘dis-ease’ in the experience of ‘letting go and holding on’ following positional relinquishment. These findings serve to extend aspects of those of earlier leadership and role exit studies, and offer previously undocumented understandings. Thus, a major contribution of this study is in the bringing-to-voice of the stories of those who step aside from leadership position yet remain in the workplace, and in the opening of avenues for further research.
Keywords: Educational leadership; Lived experience; Role exit; Succession; Case study; Hermeneutic phenomenology